Nickommoh! : a Thanksgiving celebration - Koller, Jackie French (Atheneum Books for Young Readers, 1999)
Describes a typical Narragansett Nickommoh, or harvest celebration, as it has been performed since before the arrival of the first Pilgrims in New England.